A Complex Regional Pain Syndrome Imaging Journal: Case Report. Issue 12 (6th December 2022) - Tucker-Bartley, Anthony; Li, Rupeng; Ahmed, Shihab; Birklein, Frank
Abstract : Complex regional pain syndrome (CRPS) poses a diagnostic and management challenge for many clinicians, particularly when disease symptomatology waxes and wanes. Monitoring symptom variations with digital and infrared thermal images allows for more accurate evaluation of disease progression overtime. We present the case of a patient who developed CRPS and catalog his symptoms using a digital and infrared thermal imaging diary. The images were instrumental toward establishing the initial diagnosis of CRPS, monitoring disease progression, and assessing response to treatment. We discuss the present understanding of infrared thermography in CRPS and advocate for its routine use at the beside.